Proceedings of the 1st International Conference on Character Education (ICCE 2020) 2021
DOI: 10.2991/assehr.k.210204.026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Online Learning Implementation and Student Learning Activities in the Covid-19 Pandemic Era and Its Problems

Abstract: Corona Virus Disease 2019 (COVID-19) has been declared by WHO as a pandemic and the Government of Indonesia based on Presidential Decree No.11 of 2020 concerning Determination of Public Health Emergencies. COVID-19 is a public health emergency that requires efforts to overcome it. In the education sector, the Covid-19 pandemic has accelerated education 4.0 with a distance learning system by utilizing information technology. In the education sector, teaching and learning activities, which usually take place fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Blended learning will be effectively carried out by empowering the roles of teachers and students optimally, which requires student participation as learning subjects with motivation, commitment and independence in learning (Cabras, 2020) (Setiawan, Rofi, & Jatmikowati, 2021) (Wang, Huang, & Omar, 2021). For this reason, the role of teachers and parents is a strategic role in blended learning which is a learning model during the Covid-19 pandemic and is also a challenge for teachers in TPACK competencies (Nielsen, 2009) (Zuriah & Rahmandani, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Blended learning will be effectively carried out by empowering the roles of teachers and students optimally, which requires student participation as learning subjects with motivation, commitment and independence in learning (Cabras, 2020) (Setiawan, Rofi, & Jatmikowati, 2021) (Wang, Huang, & Omar, 2021). For this reason, the role of teachers and parents is a strategic role in blended learning which is a learning model during the Covid-19 pandemic and is also a challenge for teachers in TPACK competencies (Nielsen, 2009) (Zuriah & Rahmandani, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of supporting facilities 3 (Haerul et al, 2021;Hasyim et al, 2020;Zuriah & Rahmandani, 2021) Difficulties in observing the student 2 (Magdalena et al, 2021;Elianur, 2020) Deviant behaviors 1 (Mahrani et al, 2020) Source: analyzing journal Most of the unsupporting facilities are the internet data and unsupported mobile phones.…”
Section: Challenges F Sample Of Articlementioning
confidence: 99%
“…14 studies found that Android is effective for online learning media, 6 of the research were ineffective, and 2 of the research concluded no difference for students. (Zuriah & Rahmandani, 2021;Paiman et al, 2022;Nurani et al, 2020;Maison et al, 2020;Mualim & Saputra, 2021;Kamal & Purnamasari, 2021;Wilson, 2020;Sole & Anggraeni, 2020;Permana, 2021;Subarkah, 2021;Aklimawati, et. al., 2022;Sulaiman, 2020;Mujib & Rizal;Mulyono et al, 2021).…”
Section: The Effectiveness Of Android As Online Learning Mediamentioning
confidence: 99%
“…Seafarers must know how to use nautical terminology (e.g. ship components, engine room equipment, safety-related terms); maritime communication (standard communication procedures and radio communication); technical English (phrases related to ship systems, machinery, and equipment); safety protocols (safety-related vocabulary); legal terminology (SOLAS, STCW, LSA Code); documentation (logbooks, cargo manifests, and reporting forms); cross-cultural communication; emergency procedures; environmental awareness (MARPOL -Marine Pollution); multimodal communication [16]. Ship engineers must interact with crew members from various nationalities and communicate with the crew, port authorities, and other personnel.…”
Section: Introductionmentioning
confidence: 99%